Promoting organizational citizenship behaviour through perceived organizational justice among employees of five-star hotels in Malaysia : leader-member exchange and trust as mediators - Wee Yu Ghee; Kamarul Zaman Ahmad (2009)
This study examines the role of organizational justice in promoting organizational citizenship behaviour (OCB) and assesses leader-member exchange (LMX) as well as trust in supervisor as the mediators. Data is collected from a total of 227 subordinate supervisor dyads from 16 hotels, located within the central region of Malaysia. Hypothesis is postulated on the relationship between employee’s perceived organizational justice and OCBs; it is also posited that LMX as well as trust in supervisor will mediate the effects of organizational justice on citizenship behaviour. The findings reveal that procedural justice reports stronger relationship with all dimensions of OCB, as compared to distributive justice. Both LMX and trust in supervisor are found to be significantly related to organizational justice and citizenship behaviour. However, only LMX fully mediates the impact of organizational justice on citizenship behaviour. Conceptual and managerial implications of research findings are also discussed.